Analisis Unjuk Kerja Protokol Spray and Focus di Jaringan Opportunistic - Maria Hilary; Bambang Soelistijanto (AITI, 2018)
Delay Tolerant Network (DTN) is a wireless connection which does not need infrastructure in its formation. In this research the writer test the performance of a spray and focus routing protocol in opportunistic network using ONE SIMULATOR. Performance matrix used are delivery probability, overhead, delay, and drop. Scenario used in every test are increasing the number of nodes, increasing the number of copy pesan, additional TTL (time-to-live), and addition of buffer capacity. The test result show that spray and focus routing protocol is better in working day movement when TTL is increasing because spray and focus uses transitivity to choise the best relay node so the message can reach its destination in a shorter time even though nodes are often forming a community. The delivery probabilty reached 99.4% which is mean in every 100 messages, 99 messages are sucessfully delivered to destination node.